The Effects of Foreign Resource Inflow and Savings on the Economic Growth of South Africa: A VAR Analysis - A., Temitope L. (Journal of Economics and Behavioral Studies, 2014)
This study adopts both the Vector Autoregressive (VAR) analysis and the Impulse-Response Function (IRF) to examine the importance and the effects of domestic savings and foreign direct investment (FDI) on South African economy, using data spanning over the period 1975 to 2011. While the level of domestic savings is quite low, compared to other emerging economies, South Africa has also been struggling to attract inflow of foreign resources. The form of savings in South Africa is different from the western way of savings; hence the low levels of domestic savings. The variables considered were tested for stationarity and they were all stationary before proceeding to test for cointegration and then estimate and VAR. The cointegration test revealed that there was at least one cointegrating equation; which signifies that there exists a long-run relationship among the variables. The results from the VAR Granger test of causality depicted that domestic savings lead economic growth, while economic growth leads investment. This result of the IRF also showed that while increased domestic savings is important to improve the level of economic growth in South Africa, it also leads FDI. This means that the economic environment needs to be suitable in order to attract foreign investments. The results obtained are reliable and stable as the model passes a battery of diagnostic tests. The study proposes some recommendations for policy.